Belajar Komunikasi dan empati melalui Film Jumbo dan Inovasi Promosi Wisata Indonesia melalui Industri Kreatif - Siti Syawwa Himmatul Alya; Sthiti Prabawati Pranaiswari; Talenta Maharawi; Raishalika Khairunnisa A; Arsih Amalia Chandra Permata; Wiyata Wiyata (Institut Nalanda, 2025)
This research examines the Indonesian animated film “Jumbo” on how communication between individuals and empathy are displayed in the story, as well as its promotional efforts towards the tourism sector. This research aims to reveal how these elements can be optimized in a creative industry-based promotion program. The results of this study show the importance of good interpersonal communication, teaching empathy, and strategic tourism promotion innovation. Thus, this research can be a strong basis to encourage the production of creative content that effectively integrates culture and positive interpersonal communication as tourism promotion assets.